Рец. на Василь Кононенко. Модернізація Гетьманщини: проекти козацької адміністрації 1687–1764 рр. – Київ: Інститут історії України НАН України, 2017. – 305 с. - Блануца, А. (Чорноморська минувшина, 2018)
Книга присвячена проектам реформ української адміністрації у Гетьманщині в 1687–1764 рр., які ще недостатньо вивчені як у вітчизняній, так і російській й інших зарубіжних історіографіях. У праці проаналізовано низку нововведень, які втілювалися у життя (або планувалися), за гетьмана Івана Мазепи. Нововведення за Пилипа Орлика, Івана Скоропадського, Павла Полуботка та Данила Апостола представлено у дослідженні як різні форми продовження мазепинської модернізації. У студіях над новаціями звернено увагу і на неоднозначні процеси та явища. Приміром, нововведення за гетьмана Данила Апостола носили як прогресивний (розвиток українських фінансів), так і регресивний характер (остаточний перехід судової влади у руки полковників). Монографія завершується аналізом реформування правової системи, покращення роботи канцелярій, освітніх проектів та інших планів гетьманської адміністрації за Кирила Розумовського. Також у цьому сюжеті розглядаються причини нереалізованості ряду цікавих проектів козацьких центральних установ. The research analyzes significant modernization projects of the Hetmanate Ukrainian central administration over the period from the late 1680's to the early 1760's. Part 1 of the book deals with historical sources used in research. In the next part of the research the use of Modernization Concepts in the studies of Early Modern History in post-communist Poland, Russia and Ukraine as well as the methodology of research is traced. The research uses traditional methods (analysis, comparison, synthesis), as well as сorpus linguistics, sociological and textual ones. Historical Source Research Scientific Laboratory takes the key role in the research methodology. It has been shown that the changes, implemented by Cossack central administration, belonged to the moderate modernization. The Part 3 of the book proves that Mazepa’s moderate modernization (1687-1708) provided increase in central administration efficiency, military taxes, implementation of church and educational policy, justice improvement and legal delimitation of Cossacks and common people. Part 4 of the book presents the Ukrainian Constitution (1710) of the representatives of Сossack administration in exile, innovation elements regarding protection of Ukrainian trade and justice improvement in Ivan Skoropadsky’s policy (1708-1722), as well as efforts of hetman Pavlo Polubotok (1722-1723) to adapt Ukrainian autonomy to new conditions of the Russian Empire as different attempts to implement Mazepa's model of modernization. Part 5 proves that reforms in administration, finances, justice, and army in Danylo Apostol times (1727-1734) were continuation of the main components of Mazepa's modernization. This part demonstrates that Apostol’s modernization was of both progressive (development of Ukrainian finance, beginning of army rearmament etc.) and regressive character (the final transfer of judicial power to colonels and captains, refusal of imperial projects that had to improve administration and judiciary etc.). The final part of the book researches moderate modernization in times of Kyrylo Rozumovsky (1750-1764). It describes successes of Ukrainian administration in reforming of legal system, improving administrative structures etc. It also represents the causes for most unrealized modernization projects. Рецензия посвящена анализу книги Василия Кононенко. Его книга, посвящена проектам реформ украинской администрации, в частности, в Гетманщине в 1687-1764 гг., гетьманов Ивана Мазепы, Филиппа Орлика, Ивана Скороподского, Павла Полуботка, Даниила Апостола.